REVEALING THE INDOCTRINATION OF MADURESE MARRIAGE TRADITIONS: A HEGEMONY PERSPECTIVE - Miftahur Roifah (Jurusan Sastra Indonesia, 2021)
ABSTRACT: This article investigates the hegemonic messages in Madurese marriage indoctrination among young women. This study implements a qualitative approach and the data is collected by distributing a questionnaire to young Madurese women who are studying at the University of Trunojoyo Madura. The data obtained will be analyzed through the lens of hegemony theory. The finding indicates that Madurese marriage indoctrinations contain domination used to influence the ideology of Madurese women to reinforce the status quo of women’s restriction.